A comparison of physical activity levels in childcare contexts among Finnish and Dutch three-year-olds. Issue 5 (2nd September 2016) - Soini, Anne; Gubbels, Jessica; Sääkslahti, Arja; Villberg, Jari; Kremers, Stef; Van Kann, Dave; Mehtälä, Anette; De Vries, Nanne; Poskiparta, Marita
Abstract : The aim of the current study was to determine Finnish and Dutch three-year-old preschool children's physical activity (PA) levels and how levels vary across gender, location, time of day and social contexts in both countries. A modified version of the Observational System for Recording Physical Activity in Children-Preschool (OSRAC-P) was used to measure children's PA levels and contextual variables (e.g. group composition, prompts) of children attending childcare centres in Finland and the Netherlands. In total, 90 Finnish children (46 boys and 44 girls) and 97 Dutch children (46 boys and 51 girls) were observed. Three-level linear regression analyses with cross level interactions were used to assess differences between the countries in the association between the context variables and PA. During the observations, the present sample of children was mostly sedentary in nature. Outdoor location and prompts (both positive and negative) were associated with higher levels of activity in both countries. Non-solitary playing was associated with higher activity levels in the Netherlands, but not in Finland, whereas child-initiated play was positively associated with Finnish but not Dutch children's PA levels. Finnish children were more active in the morning compared to the afternoon, while in the Dutch children PA was unaffected by time. The present findings indicate that better understanding of the contextual factors and interactions in children's PA behaviours across the two countries could help in planning childcare interventions to increase the PA levels of preschool children.